1986
DOI: 10.2466/pms.1986.63.2.801
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Childhood Hyperactivity and Accident Proneness

Abstract: Previous research suggested that hyperactive children are especially susceptible to accidents. Two questions remain: is the relationship peculiar to hyperactivity in childhood or for behaviorally disturbed children in general and does the relationship hold for females as well as for males? To answer these questions 189 patients at a child psychiatric clinic were rated on a scale which included measures of hyperactivity and accident proneness. The hyperactive patients were more likely to be described as acciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 2 publications
4
15
0
1
Order By: Relevance
“…Children with ADHD have been shown to be more accident prone than other children [53], likely because of their tendencies toward impulsive, overactive behavior. They are also more likely than other children to experience injuries due to accidents, such as broken bones, lacerations, head injuries, bruises, lost teeth, or accidental poisonings [54,55].…”
Section: Resultsmentioning
confidence: 99%
“…Children with ADHD have been shown to be more accident prone than other children [53], likely because of their tendencies toward impulsive, overactive behavior. They are also more likely than other children to experience injuries due to accidents, such as broken bones, lacerations, head injuries, bruises, lost teeth, or accidental poisonings [54,55].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, those with ADHD tend to demonstrate more dangerous driving behavior [6][8], increased involvement in traffic accidents [9], [10], increased criminality [11], [12], more risky sexual behavior [13], [14], and increased drug abuse [15]. In addition, in their meta-analytic review, Lee, Humphreys, Flory, Liu, & Glass [16] concluded that childhood ADHD was a risk factor for the dependence on, and abuse of, nicotine, alcohol, marihuana, and cocaine later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Findings that, e.g., children are more at risk from injury through accidents when fathers rather than mothers are involved in taking care of them suggests that maybe mothers have specific care giving mechanisms involving adaptive worry (Schwebel and Brezausek, 2004). Regarding risk perception, it is also of interest to consider how more impulsive children with ADHD seem to be more hypophobic of dangerous situations than children in general (Barkley, 2001;DiScala, Lescohier, Barthel, and Li, 1998;Gayton, Bailey, Wagner, and Hardesty, 1986;Swensen et al, 2004), as well as the findings that children with a highly active and risk taking temperament engage in more risk taking behavior and thus experience more unintentional injuries (Matheny, 1987;Plumert and Schwebel, 1997;Potts, Martinez, and Dedmon, 1995;Schwebel, Brezausek, and Belsky, 2006;Schwebel and Plumert, 1999). However, one needs to differentiate between disturbed risk taking behavior and normal risky play.…”
Section: Risky Play and Hypophobiamentioning
confidence: 99%